Clinical Significance and Prognosis of Renal Fusion Anomalies Detected by Tc-99m Dimercaptosuccinic Acid Scintigraphy - Esen Agar, Buket; Gurgoze, Metin Kaya; Kara, Aslihan (Sage Publications Inc, 2026)
Renal fusion anomalies develop during fetal life due to abnormal fusion and ascent of the kidneys. Horseshoe kidney is the most common partial fusion anomaly. This study aimed to evaluate renal and extrarenal complications in children with horseshoe kidney and crossed fused renal ectopia (CFRE) and to determine their clinical significance. Tc-99m dimercaptosuccinic acid (Tc-99m DMSA) scintigraphies of 759 pediatric patients were retrospectively reviewed, identifying 40 cases (5.27%) of renal fusion anomalies: 34 with horseshoe kidney, 5 with CFRE, and 1 with triple kidney. While 45% were asymptomatic, abdominal pain was the most common symptom. Vesicoureteral reflux and ureteropelvic junction stenosis were each found in 5%, and nephrolithiasis in 7.5%. Surgery was required in 7.5% of patients, with no cases of chronic renal failure. Understanding the etiopathogenesis and imaging features of these anomalies is crucial for effective clinical management.
Keywords: horseshoe kidney; renal ectopia; pediatric patient; renal fusion